Cachorro velho - Cárdenas Angulo, Teresa 1970- (Pallas, 2010)
After a hard life of constant disappointment, Perro Viejo, an old slave on a Cuban sugar plantation, has given up, until an encounter with a fellow slave and an escape to freedom make him open his heart to the world once again